2017
DOI: 10.1164/rccm.201607-1407oc
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Correlated with Severe Asthma Characteristics Reveals Heterogeneous Mechanisms of Severe Disease

Abstract: In this hypothesis-generating analysis, gene expression networks in relation to asthma severity provided potentially new insight into biological mechanisms associated with the development of SA and its phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
134
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(144 citation statements)
references
References 51 publications
10
134
0
Order By: Relevance
“…To screen for relationships between the BALF ALX ligand levels and asthma clinical parameters, a Pearson correlation matrix was constructed using measures of disease activity from all asthma subjects (NSA and SA; n = 120) (Figure 2). LXA 4 levels correlated positively with 15-epi-LXA 4 and inversely with SAA. The ALX ligands were also compared to clinical parameters of lung inflammation, asthma symptoms, and measures of lung function.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…To screen for relationships between the BALF ALX ligand levels and asthma clinical parameters, a Pearson correlation matrix was constructed using measures of disease activity from all asthma subjects (NSA and SA; n = 120) (Figure 2). LXA 4 levels correlated positively with 15-epi-LXA 4 and inversely with SAA. The ALX ligands were also compared to clinical parameters of lung inflammation, asthma symptoms, and measures of lung function.…”
Section: Resultsmentioning
confidence: 88%
“…Here, we analyzed BALF samples collected from subjects participating in the National Heart, Lung and Blood Institute's Severe Asthma Research Program-3 (SARP-3) and have identified a potentially new asthma biochemical endotype related to levels of the ALX receptor ligands LXA 4 and SAA that was associated with neutrophilic inflammation, increased asthma symptoms, and decreased lung function in SA.…”
Section: Introductionmentioning
confidence: 99%
“…These patients with SA have increased morbidity with significant adverse outcomes, including frequent outpatient visits, admissions to the hospital, and even life-threatening exacerbations (3). Cluster analyses utilizing patient clinical characteristics have identified at least 5 distinct clusters of asthmatic individuals (4,5). Identifying disease mechanisms in asthma pathogenesis is critical to move the field from clinical phenotyping to molecular endotyping of patients to enable precision medicine approaches for improved asthma management (6).…”
Section: Introductionmentioning
confidence: 99%
“…A Th2 pattern and eosinophilia may be present in mild, moderate and severe asthma, but the underlying mechanisms could be potentially very different, particularly if the subjects respond differently to treatment [28][29][30]. One of the limitations of the KUO et al [19] study is that the clustering of differentially expressed genes was conducted by pre-selecting genes in eosinophilic versus noneosinophilic sputum from both severe and moderate asthmatics on the assumption that the mechanisms of eosinophilia could be the same.…”
mentioning
confidence: 99%
“…Possibly, it is the association with factors and cytokines working with and potentiating the Th2 profile that makes the difference between clusters with overlapping gene expression. Th1 and other factors may potentiate IL-4, IL-5, and IL-13, thus promoting asthma severity and steroid resistance [28,29]. This would make it possible for Th2 cytokines in severe asthma to be synergised with other cytokines and mediators, which would affect other target cells such as mast cells, eosinophils, epithelial cells and smooth muscle and result in poor lung function, disease severity, and, more importantly, treatment resistance, a feature not seen in milder disease.…”
mentioning
confidence: 99%